2002
DOI: 10.1097/00006324-200203000-00010
|View full text |Cite
|
Sign up to set email alerts
|

The Proximity-Fixation-Disparity Curve and the Preferred Viewing Distance at a Visual Display as an Indicator of Near Vision Fatigue

Abstract: Thus, this steep proximity-FD curve indicates a weak disparity vergence system that may cause near vision fatigue. This may explain why some young adults prefer longer viewing distances at the computer workstation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 36 publications
3
46
0
1
Order By: Relevance
“…This inconsistency may be ascribable to deviations in individual capabilities and task demands, such as word-processing operators may require different monitor positions compared to scanning users. However, users with normal visual capabilities often report greater visual fatigue for viewing distances of 50cm rather than for 100cm, and these observers often consider 50cm as too close when performing typical computer workstation tasks (Jaschinski-Kruza, 1988, 1991Jaschinski, 2002).…”
Section: Viewing Distance Of Monitormentioning
confidence: 99%
See 1 more Smart Citation
“…This inconsistency may be ascribable to deviations in individual capabilities and task demands, such as word-processing operators may require different monitor positions compared to scanning users. However, users with normal visual capabilities often report greater visual fatigue for viewing distances of 50cm rather than for 100cm, and these observers often consider 50cm as too close when performing typical computer workstation tasks (Jaschinski-Kruza, 1988, 1991Jaschinski, 2002).…”
Section: Viewing Distance Of Monitormentioning
confidence: 99%
“…However, Green (2012) pointed out this traditional floating posture is not based on any sound research evidence. Over the past decade, there is increasing evidence that supporting the arms during keyboard and mouse use is a preferable working posture for most computer users (Aaras et al, 2001;Cook and Burgess-Limerick, 2001, 2002, 2004a, 2004b. Generally, properly designed armrests can reduce muscle loads on the neck, shoulders and arms (Feng et al, 1997;Weber at el., 1984), reduce pressure on the spine (Aaras et al, 1995;Andersson and Ortengren, 1974), assist in entering or leaving the chair (Alexander et al, 1991), and support task-related movements (Lueder and Allie, 2004).…”
Section: Armrests Requirementsmentioning
confidence: 99%
“…the vergence error that remains within Panum's area when a central fusion stimulus is presented (Jaschinski, 2002(Jaschinski, , 2005Jenkins et al, 1989;Pickwell et al, 1991;Yekta et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…For non-presbyopic observers, the following studies found partly higher or lower preferred monitor positions. In the studies of Grandjean, Hünting, andPidermann (1983), Jaschinski, Heuer, andKylian (1998a) and Jaschinski, Heuer, and Kylian (1999), participants adjusted both the viewing distance and vertical monitor position which resulted in a rather long viewing distance round 90 cm, probably to reduce the load on accommodation and convergence (Jaschinski 2002). In this condition, the preferred gaze inclination was around 2 108, thus was closer to the comfortable gaze inclination with closed eyes as argued above (Masseida, Perske, and Jaschinski 2013a;Masseida et al 2013b).…”
Section: Gaze Inclinationmentioning
confidence: 99%